A Poetica do olhar na obra de Guimarães Rosa - JOÃO BATISTA COSTA FILHO (2020)
ABSTRACT Guimarães Rosa’s literary work offers opportunities to explore the look potencialities in its most varied nuances. Throughout short stories and novel, like his masterpiece Grande sertão: veredas, the mineiro author presentes a varied range of unforgetable characters who compound a wealthy and complex galery of human types who are in search of understanding the world and themselves through a particular light that is, at the same time, universal. These ones are children, old and mad people, most of them “sertanejos” on the fringe oh the said civilization process, but with wisdom and perspicacy that is on the verge of the sublime. Rosa’s characters presente na original look kind, almost naive, but capable of unveiling what is hidden behind the apparent reality. This presente dissertation exctly aims to investigate this look in Rosa’s masterpiece, attempting to analyse and interpret it in the light of the specialized literary critics and theory, as well as of the philosophical contributions related to the look theme along philosophy history. The main author’s text that were selected for the presente paper were: Sagarana (São Marcos and “A hora e vez de Augusto Matraga”); Grande sertão: veredas, and Primeiras estórias (“As margens da alegria”, “Os cimos”, “A menina de lá”, “Substância” and “O espelho”). Keywords: Guimarães Rosa. Look. Literature. Revelation.